Reevaluating Health Metrics: A Multi-Dimensional Approach Beyond BMI - D, Raja; Dande Rajasekar, Vedapriya (National Journal of Community Medicine, 2023)
Body Mass Index (BMI) has long served as a conventional metric to assess overall health, but its limitations have spurred a demand for more comprehensive health evaluation tools. This article investigates the shortcomings of BMI, such as its disregard for body composition, age, gender disparities, and potential ethnic biases. By focusing on alternative indicators of health, such as waist-to-hip ratio, body composition analysis, and cardiorespiratory fitness, we highlight the need for a more holistic health assessment. Emphasizing personalized healthcare, this article advocates for integrating various health metrics to gain a deeper understanding of an individual's well-being, leading to more accurate diagnoses and tailored interventions. Ultimately, adopting a multi-dimensional approach beyond BMI offers a promising avenue for enhancing healthcare practices and improving patient outcomes.